2016
DOI: 10.2174/1874922401608010037
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Community Support for Survivors of a Natural Disaster

Abstract: Abstract:This community based participatory research study was conducted in Oso, WA. Ten survivors of the 2014 mudslide participated in a focus group and discussed their experiences before and after this natural disaster. Findings revealed that the majority of participants had feelings of confusion/redundancy and were still processing feelings of grief and loss at the time of the focus group. Another finding was the strong sense of community expressed by all participants and the high level of support participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The availability of mental health support is a key factor to the recovery. 10 Continued assessment of the students attending Keyano College and provision of low cost, high impact interventions, such as daily supportive text messaging, [65][66][67] will enhance the available literature and can help guide policy-makers to develop tailored strategies to assist this population in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of mental health support is a key factor to the recovery. 10 Continued assessment of the students attending Keyano College and provision of low cost, high impact interventions, such as daily supportive text messaging, [65][66][67] will enhance the available literature and can help guide policy-makers to develop tailored strategies to assist this population in the future.…”
Section: Discussionmentioning
confidence: 99%
“…9 Natural disasters frequently have lasting consequences on mental health, including depression, anxiety, PTSD, and alcohol and substance use disorders. [10][11][12] PTSD and depression are the most commonly assessed and treated mental health complications after a natural disaster. 13 Early diagnosis and treatment of mental health complications are key to improving prognosis.…”
mentioning
confidence: 99%
“…Much of the current research on natural disasters focuses on planning for preparedness, response, and recovery, and often overlooks the long-term mental health complications that are associated with surviving a natural disaster (14). However, the research that has been completed has found that natural disasters lead to far-reaching consequences such as major depressive disorder (MDD), generalized anxiety disorder (GAD), PTSD, and alcohol and substance use disorders (15)(16)(17)(18). The most commonly assessed and treated mental health complications after a disaster are PTSD and MDD (19).…”
Section: Introductionmentioning
confidence: 99%